2019
DOI: 10.3390/brainsci9050096
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Biomarkers in Fragile X Syndrome

Abstract: Fragile X syndrome (FXS) is the most common inherited form of intellectual disability (ID) and a known monogenic cause of autism spectrum disorder (ASD). It is a trinucleotide repeat disorder, in which more than 200 CGG repeats in the 5’ untranslated region (UTR) of the fragile X mental retardation 1 (FMR1) gene causes methylation of the promoter with consequent silencing of the gene, ultimately leading to the loss of the encoded fragile X mental retardation 1 protein, FMRP. FMRP is an RNA binding protein that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 184 publications
(223 reference statements)
0
24
0
Order By: Relevance
“…Namely, integration of diagnostic genomic data with complementary FMR1 assays and more accurate FMRP profiles is necessary [ 36 ]. The integration of these data can clarify the relationships between genotype and protein expression and the neurobehavioral phenotype [ 37 ]. Such links may improve disease prognostics and characterization of response to pharmacological and other therapeutic interventions [ 11 , 36 ], as well as help stratify patients with FXS in clinical trials [ 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…Namely, integration of diagnostic genomic data with complementary FMR1 assays and more accurate FMRP profiles is necessary [ 36 ]. The integration of these data can clarify the relationships between genotype and protein expression and the neurobehavioral phenotype [ 37 ]. Such links may improve disease prognostics and characterization of response to pharmacological and other therapeutic interventions [ 11 , 36 ], as well as help stratify patients with FXS in clinical trials [ 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…Namely, integration of diagnostic genomic data with complementary FMR1 assays and more accurate FMRP pro les is necessary [36]. The data integration enables to clarify relationships between genotype and protein expression and the neurobehavioral phenotype [37]. Such links may improve disease prognostics and characterization of response to pharmacological and other therapeutic interventions [11,36], as well as help stratify patients with FXS in clinical trials [38].…”
Section: Introductionmentioning
confidence: 99%
“…These pro-inflammatory cytokines can modulate responses in the central nervous system and can alter neurodevelopment. An aberrant immune response during neurodevelopment could lead to changes in early brain development and produce a neurological dysfunction related to ASD [ 24 , 25 , 26 , 27 , 28 ]. Some previous studies reported elevated levels of pro-inflammatory cytokines such as TNFα and IL-1β in children with ASD compared to typically developing children [ 21 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the levels of Eotaxin, MCP-1, and RANTES were significantly different for FXS + ASD compared to FXS. There was a significantly distinct profile of the cytokines: Eotaxin, RANTES, and MPC-1 in FXS + ASD compared to the controls [ 28 ]. It is unknown whether the cytokine changes are determinants in the development of FXS and if they occur throughout the lifetime of FXS [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation